Access to polyethylene elastomers via ethylene homo-polymerization using N, N′-nickel(II) catalysts appended with electron withdrawing difluorobenzhydryl group. (August 2019) - Wang, Yifan; Vignesh, Arumugam; Qu, Mengnan; Wang, Zheng; Sun, Yang; Sun, Wen-Hua
Graphical abstract: The 1-(arylimino)-2-[2, 4, 6-tris(bis(4-fluorophenyl)methyl)phenylimino]acenaphthylene-nickel(II) halides on activation with either Et2 AlCl or MAO, displayed high activities and thermally stable for ethylene polymerization affording highly branched elastomeric polyethylene show the properties resemble thermoplastic elastomers. Highlights: Facile and efficient route to produce thermoplastic elastomers. High activity for polymerization of ethylene. Branched polyethylenes by N, N′ - bis(imino)acenaphthylene-nickel(II) catalysts. Polyethylenes with excellent tensile strength and elastic recovery. Abstract: A library of five hither-to-unknown unsymmetrical N, N ′-diiminoacenaphthylenes, 1-[2, 4, 6-(4-FC6 H4 )2 CH3 C6 H4 N]-2-(ArN)C2 C10 H6 (Ar = 2, 6-Me2 PhL1, 2, 6-Et2 PhL2, 2, 6- i -Pr2 PhL3, 2, 4, 6-Me3 PhL4 and 2, 6-Et2 -4-Me-PhL5 ), have been synthesized and used to prepare their corresponding nickel(II) halide complexes of the type LNiBr2 (Ni1 –Ni5 ) and LNiCl2 (Ni6 –Ni10 ). Single-crystal structures ofNi1 andNi2 reveal the nickel center and coordination atoms formed distorted tetrahedral geometry. Upon activation with either methylaluminoxane (MAO) or diethylaluminum chloride (Et2 AlCl), Ni1 –Ni10 displayed high activities towards ethylene polymerization with the optimal performance being observed usingNi5 in combination with MAO (1.29 × 10 7 g of PE (mol of Ni) −1 h −1 at 30 °C), which produced high molecular weight elastomeric polyethylene ( M w = 4.6 × 10 5 g mol −1, T m = 47.13 °C) with narrow polydispersity ( M w / M n = 2.6). Dynamic mechanical analysis (DMA) and monotonic stress–strain test has been employed on the obtained polymeric materials and reveal high tensile strength, good elastomeric recovery (up to 93.6%) and high elongational break (up to 1037.1%), which indicates a promising equivalent material to currently commercial thermoplastic elastomers (TPEs).